Non-compaction of the ventricular myocardium associated with large patent ductus arteriosus: primary or secondary? - Wenyi Yang; Dan Yin; Kaijun Zhang; Ping Xiang; Xue Zhou; Min Zheng; Mi Li; Zhenli Cheng (BMC Cardiovascular Disorders)
Abstract Background The absence of other structural heart disease is a prerequisite for the diagnosis of non-compaction of the ventricular myocardium (NVM). We also observed that the phenomenon of non-compaction in ventricular muscle in some large patent ductus arteriosus (PDA) patients in children. This study was aimed to explore the prognosis of NVM associated with large PDA in children and provide a better understanding of the interplay between genetic and hemodynamic factors that lead to the phenotype of NVM. Methods We retrospectively analyzed the clinical data of the patients with the diagnosis of NVM with large PDA from January 2015 to January 2022 who underwent the interventional occlusion. We collected the data of the non-compacted myocardium/compacted myocardium (N/C) ratio, the size of the heart, cardiac function measured on color Doppler echocardiography and electrocardiograph (ECG) before and after interventional occlusion. Results From a total of 504 patients with large PDA underwent occlusion, 20 patients (3.94%; mean age 1.72 ± 1.44 years, 6males and 14 females) were also diagnosed with NVM. The mean diameter of the pulmonary artery end of the PDA was 7.15 ± 1.19 mm. The N/C ratio of all children significantly improved after PDA interventional occlusion with the decreased trend of LVDd and LVDs. The phenomenon of NVM regressed during the follow-up period: 9 cases(45%) after 1 M, 2 cases(10%) after 3 Ms, 4 cases(20%) after 6Ms, 1 case(5%) after 9Ms, 3 cases(15%) after 12Ms, and 1 case(5%) after 24Ms. However, there was no significant difference in the ejection fraction(EF) at all time points (P > 0.05). During the follow-up, the typical complications of NVM, include congestive heart failure, ventricular arrhythmias and thromboembolic events weren’t observed in these patients. Conclusion The phenomenon of NVM in this group maybe secondary to a large PDA. After the primary factors have been removed, hemodynamic changes and a decrease in the left heart’s preload favor the complete regression of the NVM.